Mining of efficient microbial UDP-glycosyltransferases by motif evolution cross plant kingdom for application in biosynthesis of salidroside - Bo Fan (Nature Portfolio, 2017)
Abstract The plant kingdom provides a large resource of natural products and various related enzymes are analyzed. The high catalytic activity and easy genetically modification of microbial enzymes would be beneficial for synthesis of natural products. But the identification of functional genes of target enzymes is time consuming and hampered by many contingencies. The potential to mine microbe-derived glycosyltransferases (GTs) cross the plant kingdom was assessed based on alignment and evolution of the full sequences and key motifs of target enzymes, such as Rhodiola-derived UDP-glycosyltransferase (UGT73B6) using in salidroside synthesis. The GTs from Bacillus licheniformis ZSP01 with high PSPG motif similarity were speculated to catalyze the synthesis of salidroside. The UGTBL1, which had similarity (61.4%) PSPG motif to UGT73B6, displayed efficient activity and similar regioselectivity. Highly efficient glycosylation of tyrosol (1 g/L) was obtained by using engineered E. coli harboring UGTBL1 gene, which generated 1.04 g/L salidroside and 0.99 g/L icariside D2. All glycosides were secreted into the culture medium and beneficial for downstream purification. It was the first report on the genome mining of UGTs from microorganisms cross the plant kingdom. The mining approach may have broader applications in the selection of efficient candidate for making high-value natural products.